Social-ecological Values and Practices of Indigenous Whale Fishing Community in Lamalera, East Nusa Tenggara - Aur, Alexander; Widianarko, Y. Budi; Dewi, Trihoni Nalesti (Soegijapranata Catholic University, 2023)
Lamalera is a traditional fishing village. The Lamalera indigenous people are traditional fishermen, who catch whales in the traditional sea area of the Sawu Sea. In 2014, the Sawu Sea was designated as a conservation area and National Marine Park by the central government through the Ministry of Maritime Affairs and Fisheries and the regional government of East Nusa Tenggara. Since then, the Lamalera indigenous people have been worried that the tradition of whaling will be banned and access to marine spaces will be restricted due to strict enforcement of conservation laws in the future. Thus, this research reports the aims of (1) exploring the Lamalera community’s local wisdom through the form of socio-ecological capabilities and practices of the traditional fishing community and (2) positioning the local wisdom as a cultural foundation for marine environmental governance. This research uses qualitative methods with cultural phenomenological, environmental justice, and environmental governance analysis. The results found were that the Lamalera community had social-ecological capabilities, namely lefo, tena-laja, and ola nuâng-lefa nué. Based on these findings, this research also encourages partnerships between the central government, regional governments, and the Lamalera indigenous community in supporting sustainable conservation and equitable management of the Sawu Marine National Park.